Estimating policy-corrected long-term and short-term tax elasticities for the USA, Germany, and the United Kingdom - Bernd Hayo; Sascha Mierzwa; Umut Ünal (Empirical Economics, 2022)
We estimate the elasticities of the most important tax categories using a new quarterly database of discretionary tax measures for the USA, Germany, and the United Kingdom over the period 1980Q1 to 2018Q2. Employing Romer and Romer's (2009) narrative approach, we construct a policy-neutral dataset based on revenue figures from governmental records. Using this quantitative information, we are able to subtract policy-induced changes, which often are not considered in the literature. Furthermore, we estimate state-dependent elasticities. Our conclusions are as follows. (i) In Germany and the UK, long-term tax-to-base elasticities are generally higher than short-term elasticities, whereas results for the USA are mixed. (ii) Short-term base-to-output elasticities tend to be smaller than unity, whereas long-term elasticities are close to unity. (iii) German and UK tax-to-output elasticities in the short term are lower than long-term elasticities, with mixed results for the USA. (iv) For tax-to-base elasticities, we find business-cycle asymmetries across countries but not within countries. (v) For base-to-output elasticities, our results suggest few asymmetries across countries and more asymmetries across tax types. (vi) Typically, the above conclusions do not hold for corporate income tax.
Keywords: E62; H20; H30; E32; 330; Tax revenue; Tax base; Tax elasticity; Business cycle; Germany; United Kingdom; USA